Changes in Chili Value Chain in Gunungkidul Regency Due to COVID-19 Pandemic - Ramadhan, Muhammad Vitra; Sumadio, Widyawati (UI Scholars Hub, 2024)
This study explored the changes in the chili value chain in Gunungkidul Regency due to the COVID-19 pandemic. This study used a qualitative approach by conducting in-depth interviews with chili farmers, collectors, traders, and buyers in Gunungkidul Regency. The research results show that the COVID-19 pandemic has affected all stages of the chili value chain in Gunungkidul Regency. The actors in the chili value chain in Gunungkidul Regency have successfully adapted to face disruptions due to the COVID-19 pandemic by using information technology to communicate between actors and obtain market price information. Before the pandemic, Gunungkidul Regency was one of the largest chili producers in the Special Region of Yogyakarta Province. However, due to the pandemic, chili production has decreased drastically with chili price volatility remaining. The COVID-19 pandemic has had a significant impact on the chili value chain in Gunungkidul Regency. Nevertheless, the actors in the chili value chain have successfully adapted to face disruptions due to the COVID-19 pandemic by using information technology.